Biometry of lima bean plants and seeds: contributions to genetic divergence (Research, Society and Development, 2021)
The lima bean (Phaseolus lunatus) has a wide genetic variability. To exploit this potential, descriptors are used, which are a set of details that help to register the information of the characteristics present in this genetic material. However, some information present in the descriptors needs to be updated and others added in order to describe the maximum characteristics. Thus, this research aimed to obtain information about the biometric aspects of lima bean seeds and plants that can contribute to studies of genetic divergence. The research used 70 lima beans landraces and was divided into two stages. In the first stage the characterization of the seeds and, in the second, characterization of the plant. Both, at the vegetative and reproductive phase, descriptive statistics were applied to the data to obtain percentage, average, standard deviation, classes, histograms, frequency polygons and boxplots. The results demonstrated the great genetic variability in the studied landraces. The characteristics in their majority of productive importance presented 9 different classifications. The information generated, therefore, allows contributions to studies on the improvement of seeds and grains, investigation of consumer preference and research on genetic divergence, all associated with the formation of future cultivars.